MAGNETIC THERMAL-STABILITY OF MN AND CO VOLUME-DOPED ACICULAR IRON-OXIDE PARTICLES - HAN, DH; WANG, JP; FENG, YB; LUO, HL; NA, JG (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1994)
The magnetic thermal stability of Mn and Co volume-doped acicular gamma-Fe2O3 particles was studied. These MnCo-gamma-Fe2O3 particles with a coercivity about 950 Oe and Co content about 3.5 wt % have been prepared by high temperature ion diffusing and step annealing. The MnCo-gamma-Fe2O3 particles exhibit a much higher transverse field stability than that of Co-gamma-Fe2O3 particles. The induced effective uniaxial anisotropy constant, K-u and the magnetocrystalline anisotropy constant, K-1 of the particles were determined by the analysis of torque curves. The high magnetic thermal stability of these particles is mainly due to the higher and more stable induced uniaxial anisotropy, which Is the result of the anisotropic arrangements of cobalt ions promoted by the presence of manganese ions during the step annealing. The MnCo-gamma-Fe2O3 particles show a smaller irreversible decrease of uniaxial anisotropy with temperature and time in a magnetic field.